Solve the Equation: 2ln(x)−ln (7x)=1

This is an equation laid out in terms of the natural logarithm, which essentially is the reverse function of ex . From this equation we need to find a solution for x =? Since we know that this equation involves logarithms, we should keep the logarithm laws in mind, which are;
eln(x)= xln(a) + ln(b) = ln(ab)aln(b) = ln(ab)
1) Firstly we should change the first term of the equation, using the logarithm laws 3rd logarithm law from above, so that 2ln(x) = ln(x2) 2) Combine all the terms on the left hand side of the equation to form one term, using the 2nd log law to give you : ln(x2/7x) = 13) Now we can undo the natural logarithm to give us an equation in terms of x, using the 1st log law stated above. Therefore x2/7x = e14) We can now rearrange this equation and factorise it to find solutions of x:x2=e
7x (by multiplying across by 7x)x2-7ex=0 (subtracting 7ex from both sides)x(x-7e)=0 (factorising)Therefore --> x=0 or x =7e


Answered by Dhruv G. Maths tutor

5348 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Given that: y = 3x^2 + 6x^1/3 + (2x^3 - 7)/(3x^1/2), x > 0 Find dy/dx, give each term in its simplest form


How exactly does integration by parts work?


f(x)= 2x^3 -7x^2 + 2x +3. Given that (x-3) is a factor of f(x), express f(x) in a fully factorised form.


When do I use the chain rule and when do I use the product rule in differentiation?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences